Threat mitigation in tactical-level disruption tolerant networks - Goh, Weihan (2013)
In disruption tolerant networks (DTNs), nodes exchange beacon messages to set up links via a process known as neighbor discovery. However as it is, beacon messages are susceptible to forgery and tampering that could be exploited to attack and participate in the network. This paper outlines a protocol to 1) protect beacon messages in tactical-level DTNs from forgery and tampering utilizing an identity-based signature scheme (IBS), and 2) provide capabilities for nodes that are compromised or captured to signal its state discreetly to other DTN nodes. The protocol maintains the same amount of message overhead as without it.